Religious Practices and Socio-Religious Critique in the Drama Series Bidaah: An Analysis through Soekarno’s Concept of Islam Sontoloyo - Muhamad Hasan Asyadily (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This study examines the representation of problematic religious practices in the Malaysian drama series Bidaah through the lens of Soekarno’s concept of Islam Sontoloyo. Although previous studies have explored Bidaah from the perspectives of religious discourse, maqasid al-shariah, media literacy, and religious violence, none has specifically employed Islam Sontoloyo as an analytical framework to explore religious manipulation, blind obedience, the excessive glorification of religious leaders and the use of religion for personal gain. This research adopts a qualitative approach and employs Critical Discourse Analysis to examine dialogues, narratives, and visual representations across all fifteen episodes of the series. The analysis focuses on textual representations, discursive constructions, and their broader socio-religious implications. The findings reveal four major patterns of problematic religious practice. First, religion is portrayed as a means of legitimizing authority and advancing personal interests through practices such as forced arranged marriages and nikah batin (spiritual marriage). Second, followers are depicted as accepting religious teachings without critical reflection, fostering a culture of unquestioning obedience. Third, the excessive glorification of religious leaders elevates Walid to a quasi-sacred status, obscuring the principle of tawhid and discouraging critical engagement. Fourth, religious teachings function as mechanisms of control that shape followers’ beliefs, decisions, and social relationships. In contrast, the characters of Baiduri and Hambali embody critical awareness and resistance to religious manipulation. This study contributes to Islamic and media studies by highlighting the continuing relevance of Islam Sontoloyo as a framework for understanding contemporary forms of religious manipulation, fanaticism, and religious authority in digital culture.